An extended model to predict the compressive, tensile and flexural strengths of HPFRCs and UHPFRCs: Definition and experimental validation. (15th April 2019) - Savino, V.; Lanzoni, L.; Tarantino, A.M.; Viviani, M.
Abstract: High manufacturing costs of UHPFRC and expensive and time-consuming tests performed to understand the mechanical response under loading restrict still its wider applications in the field of the structural engineering. Predictive models can be useful to reduce the number of requested tests and to optimize the amount of compounds of the mixture, for example detecting the minimal dosage of fibers necessary to attain a given tensile strength and toughness as well. Currently, not many predictive models do exist and one of the most recent, developed in order to estimate the compressive and tensile responses of HPFRCs, was not notably suitable for UHPFRCs. The main purpose of this work concerns the extension of such a model, in order to predict the mechanical response (in flexion as well) of a given HPFRC/UHPFRC for any change of matrix and fiber properties. Theoretical results were compared with experimental data, thus conforming some shortcomings of the previous model. Once the matrix and fiber properties of a marked UHPFRC were selected, the extended model was used to predict the tensile and flexural bending responses of a full scale UHPFRC structural beam, showing good agreement with the experimental results.